Improving the Performance of Supply Chain Collaboration and Supplier Development Practices in Developing Countries: A Case study of Two Nigerian Manufacturing Firms - Ezugo, Oguebie (2011)
Purpose – The purpose of this research is to explore the factors affecting the performance levels of supply chain collaboration and supplier development in a developing country’s manufacturing supply chain; and subsequently, give recommendations on ways to improve the operational performance of these practices.